A Relationship between Physical Infrastructure and Patient Satisfaction: A Case Study of Kantipur Dental Hospital - Pandey, Gita; Adhikari, Surakshya (NPRC Journal of Multidisciplinary Research, 2024)
This study investigates the impact of physical infrastructure on patient satisfaction at Kantipur Dental Hospital, a prominent dental care facility in Nepal. With the increasing demand for high-quality healthcare services, understanding the factors influencing patient satisfaction is crucial for healthcare providers. The research aims to explore how various aspects of the hospital’s infrastructure—specifically, the use of state-of-the-art equipment, cleanliness and hygiene, sterilization practices, and convenient location—affect patients' perceptions of care quality. A quantitative research design was employed, utilizing a structured questionnaire distributed to 117 patients who had received treatment at Kantipur Dental Hospital within the last six months. The questionnaire measured patients' perceptions of the clinic's infrastructure and their overall satisfaction, with a focus on two key dimensions: confidence after treatment and the acceptability of service fees. Data analysis was conducted using Spearman’s rho correlation to assess the relationships between the perceived infrastructure variables and patient satisfaction outcomes. The findings reveal significant positive correlations between perceptions of the hospital's physical infrastructure and patient satisfaction. Specifically, the use of modern equipment and a clean, hygienic environment were strongly associated with increased patient confidence post-treatment. Furthermore, the accessibility of the hospital location was also found to influence perceptions of service fee acceptability. Notably, while sterilization practices contributed positively to patient confidence, they did not significantly impact fee perceptions, suggesting that patients prioritize cleanliness and modernity in their overall evaluation of care. These results underscore the critical role of physical infrastructure in enhancing patient satisfaction at Kantipur Dental Hospital. The study recommends that healthcare facilities continue to invest in modern technology and maintain high standards of cleanliness to foster patient confidence and satisfaction. This research provides valuable insights for clinic management and policy-makers, emphasizing that improving physical infrastructure is essential for delivering quality healthcare services and ensuring positive patient experiences.